Escritura e intencionalidad en Maurice Blanchot - Rodríguez, Joan Cabó (Cauriensia, 2022)
This article proposes an approach to the extreme and eccentrically phenomenological conception of intentionality in the work of Maurice Blanchot. In the wake of some studies that have highlighted the relations of the French writer with phenomenology and starting mainly from his critical work, although also attending to some of his works of fiction, it is drawn on it an approach to the relationships between writing and intentionality in Blanchot, in three sections: (1) writing as an exit from oneself or ecstatic experience, (2) the limit intentionality of writing and (3) the failure of the intention and the event of the other. Beyond Blanchot's obvious breakup with the Husserlian approach, his reflection on the intentionality of writing finds points of contact with some proposals of contemporary phenomenology and, especially, with the philosophy of Emmanuel Levinas.